1999
DOI: 10.1093/rheumatology/38.10.948
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plasma free fatty acid concentrations in rheumatoid arthritis patients during fasting and their effects upon T-lymphocyte proliferation

Abstract: Fasting-associated increases in total plasma FFA concentrations do not inhibit, but rather enhance, in vitro lymphocyte proliferation. An inhibitory effect could only be achieved by manipulating the balance between the unsaturated and saturated fatty acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 16 publications
2
37
0
Order By: Relevance
“…In fact, inhibition of insulin signal transduction was observed at concentrations of 75 nM and above with the maximal inhibition observed at 750 M. The concentrations, which activate signal transduction, are slightly below what has been observed in circulating plasma (400 -600 M, total FFA and 100 -200 M, palmitate) but are well within the range for the concentrations observed in muscle tissue, where muscle palmitoyl-CoA has been observed in the range of 1 nM in type 2 diabetics (33)(34)(35). These concentrations appear to fit well within range of the concentrations observed in vivo, suggesting that these observations are relevant to the study of high fat diet-and obesity-related insulin resistance and inflammation (33,35).…”
Section: Discussionmentioning
confidence: 46%
“…In fact, inhibition of insulin signal transduction was observed at concentrations of 75 nM and above with the maximal inhibition observed at 750 M. The concentrations, which activate signal transduction, are slightly below what has been observed in circulating plasma (400 -600 M, total FFA and 100 -200 M, palmitate) but are well within the range for the concentrations observed in muscle tissue, where muscle palmitoyl-CoA has been observed in the range of 1 nM in type 2 diabetics (33)(34)(35). These concentrations appear to fit well within range of the concentrations observed in vivo, suggesting that these observations are relevant to the study of high fat diet-and obesity-related insulin resistance and inflammation (33,35).…”
Section: Discussionmentioning
confidence: 46%
“…Findings from serum metabonomics partially ascertained the previous report that FFAs would increase in RA individuals [20,21]. A report indicated that fasting-associated increases in total plasma FFAs promoted lymphocyte proliferation in vitro and might not facilitate to alleviate inflammation [22]. Generally speaking, lysophosphatidylcholines involve in inflammation and inflammation is a key pathological event in RA.…”
Section: Effect Of Ynb On the Down-stream Metabolism Of Aa In Osteoblmentioning
confidence: 55%
“…The concentrations of palmitic acid used here are within the reported pathophysiologic range. 16,17 Exposure to Palmitic Acid Results in Intracellular Lipid Accumulation in Hepatocytes. Human hepatoma cells (HepG2) were cultured with different concentrations of palmitic acid for varying intervals.…”
Section: Resultsmentioning
confidence: 99%